Pengaruh Kepemimpinan, Motivasi Dan Disiplin Kerja Terhadap Kinerja Guru Smk Farmasi Ikasari Pekanbaru - Rini Fatriani; fahrial (Ikatan Sarjana Ekonomi Indonesia Cabang Pekanbaru, 2020)
The population in this study are all teachers SMK Farmasi Ikasari Senior High School Pekanbaru, amounting to 55 people. Sampling was performed using saturated sample. Data analysis is done by using validity, reliability, classical assumptions, multiple linear regression, F test and t-test. The tests are performed in order to determine the relationship between the independent variable with the dependent variable. Based on the result of the research, the leadership, motivation, and performance are influenced on teacher’s performance. It is proved by finding the score of R=0.769. It means that there was a correlation among leadership, motivation and discipline on teachers’ performance at SMK Farmasi Ikasari Senior High School Pekanbaru. Meanwhile the score of R was 56,7%. It means that there was a contribution of leadership, motivation, and discipline on teachers’ performance. Furthermore, it has positive contribution on teachers’ performance by finding F score is 24.800 and level significant is 0.000. Partially, there was a positive significant effect of leadership variable, motivation, and discipline on teachers; performance at SMK Farmasi Ikasari Senior High School pekanbaru. The details of the linear regression as follow: Y = 14.359 + 0,149X1 + 0,185X2 + 0,376X3 and sig. 0.048, 0.040, 0.000 are lower than Alpha 5%. The conclusion of the research was the hypothesis partially and altogether among leadership variable, motivation, and discipline on teachers’ performance was proved and accepted.